Local productions around Vesuvius: trade patterns and identity - Serena Martucci, Caterina; Ferdinando De Simone, Girolamo; D’Italia, Serena (Rei Cretariae Romanae Fautorum Acta, 2015)
This contribution aims to provide some insights into the identities of late antique communities of Campania – from Neapolis to the western fringes of Hirpinia – through the use of trade patterns.